Evaluating the Growth and Yield Variability of Selected Cowpea (Vigna unguiculata L. Walp.) Cultivars Infected with Cowpea Aphid-borne Mosaic Virus and Southern Bean Mosaic Virus - E. W. Mamman; M. T. Salaudeen; A. C. Wada; A. S. Paiko (Current Research Progress in Agricultural Sciences Vol. 9, 2025)
Cowpea is susceptible to a complex of insect pests and diseases and they attack the crop from vegetative stage to storage, which forms part of the most important impediments to its profitable production. Virus diseases are the most damaging diseases of cowpea and represent a significant proportion of losses regarding the potential value of the crop in sub-Saharan Africa. This study was, therefore, conducted to determine the resistance of selected cowpea cultivars to single and mixed infections of CABMV and SBMV and to ascertain the effects that these two viruses have on the selected cowpea cultivars in single and mixed infections. Eight cowpea (Vigna unguiculata L. Walp.) cultivars were evaluated for Cowpea Aphid-Borne Mosaic Virus (CABMV), Southern Bean Mosaic Virus (SBMV), CABMV+SBMV, and SBMV+CABMV resistance under greenhouse conditions at the School of Agriculture and Agricultural Technology Minna, Nigeria in 2016 (lat.9o40’N; long 6o30’E at an altitude of 220 m.a.s.l). Virus-infected plants were evaluated independently using a Completely Randomized Design with three replications. In single infections, cowpea seedlings were inoculated at 10 days after sowing (DAS), while in mixed infections the second virus inoculation was performed at 21 DAS. Disease incidence, symptom severity, plant growth and yield characters were recorded. Disease severity was evaluated based on a visual scale of 1-5. The data were subjected to analysis of variance and Duncan’s Multiple Range Test was used for mean separation. Results showed that one hundred percent infection was obtained regardless of the cultivar. The single and double virus infections reported in this study had significant and different effects on the eight cowpea cultivars evaluated which can be attributed to the different susceptibility levels of the cultivars to the respective viruses. High disease severity with a symptom score of 4.0 was recorded for all the cowpea cultivars infected with CABMV alone and CABMV+SBMV, while moderate resistance with a symptom score of 3.0 was recorded only in cultivars IT09K-231-1 and IT10K-973-1 to SBMV, and in IT07K-299-6 and IT10K-973-1 to SBMV+CABMV. Through the four virus treatments, seed weight per plant was significantly (p<0.05) highest in IT10K-843 infected with CABMV which, produced 3.5 g; cultivar, IT07K-299-6 inoculated with SBMV produced 4.9 g, while IT10K-973-1 under CABMV+SBMV infections produced 4.9 g; and IT07K-298-9 infected with SBMV+CABMV produced 4.4 g. The cowpea cultivar IT07K-299-6 which gave the highest seed weight under single and double virus infections can be exploited in hybridization studies to develop resistant cowpea varieties for use by farmers. Intensive biotechnological research that will result in the development of cowpea cultivars with multiple resistance to economically important viruses should be explored.